Study of the Effect of Cathode Graphite on I-V Characteristics of Argon DC Glow Discharge - A. khadayeir , Abdulhussain; H. yousif , Falah (University of Thi-Qar Journal of Science, 2021)
In this paper, the electrical properties of the glowing Argon discharge were studied for the purpose of knowing the parameters of the stable plasma work. The Argon plasma generated from the DC glow discharge has been examined. The glowing discharge system consists of two electrodes , The cathode is made of graphite with a disk of 8cm diameter and 1.7cm thickness. The anode is made of aluminum material with a disk of 8.8cm diameter and 1.1cm thickness. The electrical electrodes are enclosed in a glass cylinder made of pyrex containing argon gas. Several parameters which affect on the state of electric discharge, including gas pressure and the distance between electrodes.(I-V) curves of electrical discharge were measured at different pressures(0.075,0.32,0.65,0.75 and 1.12 torr) and distance between electrodes(2,4,6 and10 cm). By observing the electrical properties (I-V), it is concluded that the electric discharge of the plasma argon gas works within the abnormal glow area and is an important parameter in the deposition process. The higher discharge current of the argon plasma increases with increased pressure, the higher deposition rate was achieved.